The Influence of Social Media Usage and User Intention on QRIS Adoption Strategy in Mobile Banking with Trust as a Mediating Variable on MSMEs Business Actors - Giofani, Fachrizal; Danarsari, Dwi Nastiti (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study analyzes the influence of Social Media Usage and Intention to Use on the adoption of QRIS in mobile banking by Micro, Small, and Medium Enterprises (MSMEs), with trust as a mediating variable. The study is motivated by the growing need for digital financial services and the role of QRIS as a standard for an efficient and inclusive national payment system. A quantitative approach was used by distributing questionnaires to MSMEs in Jabodetabek. Using the Slovin formula with a population of 32.7 million QRIS merchants (as of June 2024), a minimum sample of 100 was determined. After data cleansing to remove invalid or outlier responses, 85 valid responses were analyzed using Structural Equation Modeling (SEM). The results show that Social Media Usage and Intention to Use do not directly affect QRIS adoption, with T statistics of 0.860 (p = 0.390) and 1.496 (p = 0.135), and path coefficients of 0.088 and 0.165, respectively. However, both significantly influence trust (T = 5.298 and 5.729, p = 0.000), with path coefficients of 0.442 and 0.489. Trust significantly affects QRIS adoption (T = 7.072, p = 0.000, coefficient = 0.881). Indirectly, Social Media Usage and Intention to Use impact adoption through trust (T = 5.041 and 3.915, p = 0.000), with coefficients of 0.390 and 0.431. These findings highlight trust as a key driver of QRIS adoption, suggesting that digital communication strategies via social media can enhance trust and promote fintech adoption among MSMEs.